Improved General Correlation for CHF in Uniformly Heated Vertical Annuli With Upflow. Issue 6 (12th April 2016) - Shah, Mirza M.
Abstract : A general correlation for critical heat flux (CHF) in uniformly heated vertical annuli with upflow is presented. It is an improved version in equation form of the author's 1980 graphical correlation. The correlation is compared to test data from 58 data sets from 25 studies. The data include annuli with internal, external, and bilateral heating, 10 fluids, reduced pressures from 0.016 to 0.905, flow rates from 100 to 15, 759 kg/m 2 -s, tube diameters from 1.5 to 96.5 mm, annular gaps from 0.3 to 16.5 mm, ratio of length to heated equivalent diameter from 1.3 to 394, inlet qualities from –3.3 to +0.91, and critical qualities from –2.7 to +0.95. All data points are predicted with a mean absolute deviation of 16.5%. No other well-verified general correlation is available. Considering the good agreement with this wide range of test data, this correlation should be of considerable help in design and analysis.